Laboratory Simulation of Aeolian Sand Transport and Physical Modeling of Flow Around Dunes - White, Bruce R (Annals of Arid Zone, 2016)
This paper discusses the possibilities of laboratory simulation of large-scale flow around dunes, both with and without saltation, and the study of the physics of the small-scale particle motion occurring on a sand surface composed of like-moveable particles, Physics of the atmospheric boundary layer are presented in the context of laboratory applications. The governing equations of fluid and/or’particle motion. are discussed and analyzed for applications in laboratory testing. The most important similitude parameters, as applied to wind-tunnel requirements for conservation of mass, momentum, energy, and the boundary conditions are presented and discussed. Key findings and results are that: i) in general, flow around a dune or multiple dunes with saltation present cannot be accurately simulated in wind tunnels; ii). flow field around all or part of a full-scale dune can be. simulated marginally in a wind tunnel, provided "large" model scales and "reasonably high" wind-tunnel speeds are used (the conditions of "large" model scales and "reasonably high" speeds are specified within the text); and, iii) it is possible to accurately replicate the process of saltation in wind tunnels provided appropriate similitude and independence criteria of Reynolds and Froude numbers are observed. Limited laboratory and wind-tunnel studies are cited.